Automatic stabilization and discretionary fiscal policy in the financial crisis - Mathias Dolls; Clemens Fuest; Andreas Peichl (IZA Journal of Labor Policy, 2012)
This paper investigates the relationship between the magnitude of automatic stabilizers in the tax and transfer systems of 19 EU countries and the US, and discretionary fiscal stimulus packages passed by these countries during the recent economic crisis. In particular, we ask whether countries with larger automatic stabilizers have enacted smaller discretionary fiscal stimulus programs. Our results support this hypothesis. Our findings also suggest that social transfers, in particular the rather generous systems of unemployment insurance in Europe, play a key role for the stabilization of disposable incomes and explain a large part of the difference in automatic stabilizers between Europe and the US.
Keywords: E32; E63; H2; H31; 330; automatic stabilizer; economic crisis; taxes and benefits; fiscal policy; Finanzkrise; Schock; Steuersystem; Öffentliche Sozialleistungen; Antizyklische Finanzpolitik; Automatischer Stabilisator; Wirkungsanalyse; Vergleich; EU-Staaten; USA